Pemanfaatan Fitur Remote Control Melalui Media Bluetooth pada Telepon Seluler Sebagai Alat Bantu Proses Pengajaran - Hartono, Indra Kusumadi (Bina Nusantara University, 2011)
Teaching methods commonly require dynamic presentation techniques. Cellular phone technology can be utilized as a remote control via Bluetooth. Several experiments are conducted in simple ways to measure the effective distance between the device cell phone-notebook and PC-cell phone. Based on the research, it is concluded that local cell phones turned out to be acceptable as a teaching device utilized at campus.